Enhancing Quality Culture through an Integrated Quality Management Model for Hajj and Umrah Guidance Centers in Padang City - Mulyawan, Hami; ., Rusdinal; ., Hadiyanto; ., Sufyarma; Gistituati, Nurhizrah (Journal of Cultural Analysis and Social Change, 2025)
This study develops, validates, and evaluates an Integrated Total Quality Management (TQM) Model as a strategic approach to enhancing quality culture in Hajj and Umrah Guidance Centers (HUGC) in Padang City. The research is driven by the suboptimal quality management practices and service delivery systems in HUGCs, which have yet to adopt an integrated and sustainable quality management framework. Using a Research and Development (R&D) proceeds through four stages: (1) research and data collection, (2) planning and preliminary model development, (3) field testing and model revision, and (4) final product testing and dissemination. Data were gathered through questionnaires, interviews, observations, and expert validations involving administrators, instructors, and pilgrims. The results show that the Model demonstrates strong feasibility, with accessibility reaching 73.99% and acceptability reaching 66.87%. Expert Validation confirms that both the model book and guidebook are appropriate for implementation. Practicality testing indicates that the Model can be effectively applied in the field, while effectiveness testing reveals significant improvements in leadership, collaborative culture, communication, instructor commitment, and service accountability. These findings suggest that the Integrated TQM Model is a valid, practical, and effective approach for strengthening institutional performance and enhancing the professionalism of Hajj instructors. The study concludes that the Model is feasible for adoption by the Ministry of Religious Affairs and HUGCs through continuous training and structured implementation. Its primary contribution lies in integrating Islamic values into quality management practices, thereby reinforcing institutional governance and promoting sustainable pilgrim satisfaction.